The Content of the Main Concepts of Competition and Industrial Policies Harmonization - Zainutdinova, Elnara (Journal of History Culture and Art Research, 2018)
The purpose of this work is the development of conceptual model of competition and industrial policies harmonization, ensuring their complementarity and strengthening with obtaining a synergistic effect. The scientific definitions of competition policy and industrial policy are specified on the basis of the identified criteria combination in terms of the possibility of harmonization. The schemes of both approaches interaction are presented: uncoordinated, synchronous, harmonious and assessment of their efficiency on the basis of specific, synchronous and combined indicators of competition and industrial policies. The conceptual graphic model of the harmonization of competition and industrial policies process is presented. The scientific definition of the category «competition and industrial policies harmonization» as a dynamic, variable process of coordination and synchronization through system of complementary indicators of state measures into one long-term vector aimed at sustainable balanced development of industries based on combination of tools and advantages of both approaches is given.